36. HPV VACCINATION PRACTICE OF STUDENTS OF THE FACULTY OF PHARMACY OF HANOI NATIONAL UNIVERSITY OF MEDICINE AND PHARMACY IN 2023 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of HPV vaccination practices among students of the Faculty of Pharmacy at University of Medicine and Pharmacy - Hanoi National University in 2023 and some related factors.Research objects and methods: Cross-sectional descriptive study via online survey conducted on 234 students of VNU, University of Medicine and Pharmacy in 2023.Results: There were 70 students (29.9%) vaccinated against HPV, of which 23.9% of students had received all 3 doses of HPV vaccine. Women have a significantly higher rate of practice than men (29.3% compared to 5.7%). The HPV vaccination rate was highest among students from the city (42.6%) and lowest among students from mountainous areas (7.1%). Students who share with their families about sex, have acquaintances with cervical cancer, hear information about HPV from medical staff and the media, receive vaccination advice from relatives, health care workers, or students with knowledge about cervical cancer and HPV, had a significantly higher rate of HPV vaccination practice than the other groups (p < 0.05).Conclusion: Practice of full-dose HPV vaccination among students at University of VNU, Medicine and Pharmacy is still low, accounting for 23.9%. Personal characteristics such as year of study, gender, place of residence, relationship and information access characteristics of students are related to HPV vaccination practices.
Keywords: HPV, cervical cancer, HPV vaccination practice, HPV prevention.